RESEARCHES ON COMPRESSIVE MECHANICAL BEHAVIORS OF ADHESIVE BONDED THIN-WALLED HOLLOW SPHERES STRUCTURE - DAI MeiLing; YANG FuJun; HE XiaoYuan; DAI XiangJun (Jixie qiangdu)
Compressive mechanical properties of thin-walled hollow spheres structure were researched by experiment and finite element method. Ping-Pong balls were selected and bonded together with a linking neck to comprise the ideal model of thinwalled hollow spheres structure. The experimental result validated the effectiveness of the finite element model. The effects of the material and geometry parameters of the hollow spheres and the linking neck were then investigated by finite element method. The results reveal that:（ 1） the deformation process of the structure includes four stages: elastic deformation,axisymmetric buckling,forming non-axisymmetric polygon and transforming to axisymmetric mode;（ 2） the elastic modulus and yield stress basically increase with the hollow sphere wall thickness,linking neck radius and center thickness as well as the Young’s modulus and yield stress of spheres material;（ 3） the strain of structural self-contact behavior increases with the linking neck center thickness and radius.